Awaiting blood pressure stabilization in ambulatory pregnant women: is 5 minutes sufficient?. (18th August 2017) - Patel, Shivani; Korst, Lisa M.; Ouzounian, Joseph G.; Lee, Richard H.
Abstract: Objective : Current recommendations for timing of blood pressure measurement in ambulatory pregnant women vary and are based on studies in the nonpregnant population. The objective of this study was to determine if there is a difference in systolic blood pressure (SBP) and diastolic blood pressure (DBP) between minute-5 and minute-10. Methods : A prospective study was conducted at our prenatal care clinics. Participants had their blood pressure measured upon sitting and every 5 minutes for 15 minutes. Initial SBP and DBP were compared to measurements at each time point. Additionally, the SBP and DBP at minute-5 were compared to minute-10. All statistical tests were two-sided. Results : Data from 400 patients were analyzed. Of these, 34.0% were in the first, 30.7% were in the second trimester, and 35.2% were in the third trimester. In each trimester, there was a significant difference in the SBP and DBP at minute-5 compared to minute-0. At minute-10 compared to minute-5, there was no further drop for all trimesters, except for a small drop in DBP in the second trimester (−1.3 ± 6.0, p  = 0.012). Conclusion : In an ambulatory setting, 5 minutes after sitting appears to be an appropriate time point to measure blood pressure in pregnancy.